The Relationship Between Anxiety and Self-Confidence in English Language Learning - Rizki Silvia Ariyani; Roslide Yosintha (Journal of English Education, 2022)
Anxiety is a condition or disorder in which the sufferer experiences excessive anxiety, which manifests as a racing heart, cold sweats, trembling, and shortness of breath. Students experience a great deal of anxiety while learning English, frequently misinterpreted as a lack of self-confidence. According to some studies, a person's anxiety level affects their level of self-confidence. This article examines the relationship between anxiety and students' confidence in learning English. The researchers used quantitative methods and found that the relationship between anxiety and self-confidence was relatively weak based on the data collected.